Commercial Praxis of Neo-Pentecostal Churches and the Prosperity Gospel - Mudimeli, Lufuluvhi; Muthivhi, Mashudu E.; James, Gordon (Commercialisation of Religion in South Africa: A Pentecostal Approach, 2023)
The incursion of prosperity theology into the doctrinal space of some Charismatic and Neo-Pentecostal churches has generated fierce debate. The prosperity discourse promotes a spiritualised economy of materialism, commercialised around the idea of prosperity as a sacred right for spiritual progress. The prosperity gospel praxis in the context of Neo-Pentecostal churches in Thohoyandou is cause for theological concern, having in some cases led to unbiblical practices and beliefs. The prosperity gospel and the commercial praxis within Neo-Pentecostal churches has a significant impact on followers. Critics argue that it is a form of exploitation, and that it preys on the vulnerable and takes advantage of people’s desire for material success; critics contend furthermore that it is a distortion of the true message of Christianity, which is founded on the work of the Holy Spirit. As part of a prosperity-oriented interpretation, a selection of proof texts are isolated and equated with divine certainties without full consideration of the original intent of the scriptures concerned. This is problematic because, in practice, representing the message of the gospel as an apparatus for monetary gain will cause the meaning of the Gospel message to be lost, and will result in adverse repercussions for adherents. From a Practical Theology vantage point, this article reflects on practical application in pastoral situations based on solid theological foundations and subsequently assesses the problematic praxis of prosperity theology. The intention is to offer remedial pastoral guidance through theological arguments as a means of reorientation towards a new praxis that affords paradigms and models to help practitioners and adherents navigate the complexities of the prosperity gospel.
paid